Intégrer une communauté dans une autre : Barack Obama et Amazing Grace - Fiona Rossette (Argumentation et Analyse du Discours, 2018)
The eulogy delivered by Barack Obama in homage to Clementa Pinckney, the black pastor who was assassinated in his church in Charleston, triggered much commentary in the media, due to the peroration, when Obama actually broke out into song, singing several verses from the most famous hymn of the English language, Amazing Grace. In this study, I examine the ways in which the speech generates the sense of communion that is so central to epideictic oratory. I demonstrate how Obama succeeds, from a discursive point of view, in integrating his live audience (the Black American community) within the overarching community of the American people. In order to do so, I draw on the concepts of “Rhetorical Staging” (Maingueneau 2016) and “particitation” (Maingueneau 2004). I examine the specific status of the orator, who “rises above” his/her audience, precisely in order to bring different components of the audience together within the same community. The different forms of participation by the audience, which are part of Afro-American religious ritual, play a crucial role in bringing about the communion. This is also achieved via a staging of the word, rhetorical figures, vocal and rhythmic variation, and body language. These phenomena culminate in the song, and involve the whole body. Such an embodiment plays a major role in the integration of the audience into the overarching community.